2022
DOI: 10.1002/admi.202201164
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser‐Texturing the Surface of Ti‐Based Implants to Improve Their Osseointegration Capacity

Abstract: Ideally, dental implants should achieve rapid and maintain long-term mechanical stability, which is determined primarily by their integration into the underlying supporting bone. [3] This osseointegration capacity can be markedly improved through modifications of key surface properties, including roughness, wettability, oxide layer thickness, and surface chemistry. [4][5][6] Currently, anodization, sandblasting and acid-etching are widely used, individually or in combination, to modify the surface properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…[ 61–63 ] In this study, we assessed the capacity of BMGs to steer the osteogenic response of HBCs while taking into account the influence of blood–material interactions using a well‐established in‐vitro assay with enhanced physiological relevance. [ 32,64–66 ] The BMGs’ capacity to support HBC attachment was comparable to that of Ti64 ( Figure A). After only 24 h, HBCs had developed an elongated cell morphology and spread over the fibrinogen‐decorated surface of BMGs and Ti64 (Figure 7A).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[ 61–63 ] In this study, we assessed the capacity of BMGs to steer the osteogenic response of HBCs while taking into account the influence of blood–material interactions using a well‐established in‐vitro assay with enhanced physiological relevance. [ 32,64–66 ] The BMGs’ capacity to support HBC attachment was comparable to that of Ti64 ( Figure A). After only 24 h, HBCs had developed an elongated cell morphology and spread over the fibrinogen‐decorated surface of BMGs and Ti64 (Figure 7A).…”
Section: Resultsmentioning
confidence: 91%
“…[ 78 ] Ultimately, this could provide a more accurate alternative to stochastic processes currently used for the treatment of implant surfaces, including anodization, sandblasting, and acid‐etching. [ 32,64 ] The introduction of surface features could be used to further improve the capacity of BMGs to enhance osteogenesis in comparison to Ti64, as demonstrated here in the absence of any topographical features and notable surface roughness. Furthermore, the introduction of specific nano‐scale topographies could be used to further improve the antibacterial properties of BMG‐based implants beyond the level reported here.…”
Section: Discussionmentioning
confidence: 99%
“…A nonlinear least squares algorithm (e.g., 36 ) was used to determine the model coefficients δ pen and q*. For model 2, the threshold fluence for ablation was fixed at the measured value and F thresh,optical was determined as a function of δ pen2 and q 2 * using Equation (17). Figure 3 shows measured and modeled characteristic curves for ablation of enamel.…”
Section: Ablation Efficiencymentioning
confidence: 99%
“…Intentional surface texturing for improved bonding of restorative materials and surface patterning of dental implants for improved osseointegration capacity are further areas where femtosecond lasers have a valuable role to play. [15][16][17][18][19][20] The higher precision achieved with fs lasers compared to other laser types is attributed to the reduced size of the heat affected zone 17 and the range of surgical applications for fs lasers is expanding in areas where minimal collateral damage and high precision are required. 20 For dental applications, the proper choice of laser parameters for the fs laser is essential for high-quality laser processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that the femtosecond laser can create both hydrophobic and hydrophilic surfaces. Lackington et al investigated the biocompatibility of titanium-based implants with femtosecond laser modified surfaces and reported that hydrophobicity can be affected by surface topography and chemical composition [43].…”
Section: Materials Characterizationmentioning
confidence: 99%